2017
DOI: 10.3855/jidc.8138
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ESBL-producing Escherichia coli recovered from companion dogs in Tai'an, China

Abstract: Introduction: Animals are considered to be reservoirs of extended-spectrum beta-lactamase (ESBL)-producing bacteria, but few epidemiological data on ESBL-producing Escherichia coli urinary tract isolates in pet dogs are available in China. Methodology: This study was conducted to describe the prevalence and characterization of ESBL producers among E. coli urinary tract isolates from pet dogs in Tai'an, China. Results: A total of 118 E. coli were obtained from urinary samples of 80 companion dogs suffering from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
0
2
1
Order By: Relevance
“…Other studies have also evaluated the presence of ESBL-Ec in dogs suffering from UTI worldwide. Among the isolates of E. coli in this study, the observed frequency of 6,6% (11/22) of ESBL producers is higher but not so far than that found previously in the United States (4%), Switzerland (3,4%) and China (3,8%) ( Huber et al 2013;Li et al 2017;O'Keefe et al 2010), although data from those studies were single-institution based and may not be entirely comparable.…”
Section: Discussioncontrasting
confidence: 78%
“…Other studies have also evaluated the presence of ESBL-Ec in dogs suffering from UTI worldwide. Among the isolates of E. coli in this study, the observed frequency of 6,6% (11/22) of ESBL producers is higher but not so far than that found previously in the United States (4%), Switzerland (3,4%) and China (3,8%) ( Huber et al 2013;Li et al 2017;O'Keefe et al 2010), although data from those studies were single-institution based and may not be entirely comparable.…”
Section: Discussioncontrasting
confidence: 78%
“…The prevalence of ESBL-producing E. coli was shown to be about 3% in clinical samples from companion animals in the US [8,9]. ESBL urinary tract infections (UTIs) in dogs have been reported in China and Switzerland in about 5% of samples [10,11]. In some laboratories (e.g., UK and China), there is an increasing percentage of extended-spectrum cephalosporin-resistant E. coli found in clinical isolates from companion animals [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The urinary tract disease guidelines for dogs suggest that veterinarians should be aware of the pathogen and antimicrobial resistance trends among urinary pathogens isolated from patients in their clinic [7] The prevalence of ESBL-producing E. coli was shown to be about 3% in clinical samples from companion animals in the US [8,9]. ESBL urinary tract infections (UTIs) in dogs have been reported in China and Switzerland in about 5% of samples [10,11]. In some laboratories (e.g., UK and China), there is an increasing percentage of extended-spectrum cephalosporin-resistant E. coli found in clinical isolates from companion animals [12,13].…”
Section: Introductionmentioning
confidence: 99%